Identification of dengue virus proteome B-cell epitopes using an immunoinformatic approach - Neeraj Kumar Dixit, Anup Kumar (Journal of Applied Pharmaceutical Science, 2021)
Dengue is a disease caused by one of DENV1, DENV2, DENV3, and DENV4 serotypes. There is no successful vaccine available to control all serotypes of dengue virus. Therefore, we are discovering new prevention measures using immunoinformatics strategies to establish an epitope based subunit vaccine that can produce different immune responses within the host. The prediction and subsequent discovery of B-cell epitopes using in silico techniques will improve the authors’ knowledge in pathogenesis of diseases and the development of better vaccines. In present work, for the analysis of serotype DENV2 proteomes, three separate prediction approaches, such as ABCpred, BCpred, and AAP method were used, which leads to the prediction of 1458 B cell epitopes. Antigenicity, allergicity, and toxicity were analyzed for selected 66 epitopes. Eight antigenic epitopes were predicted among 27 consensus epitopes. The IEDB conservancy tool evaluated six of them and found to be more than 75% conservancy. The research using the IEDB conservancy tool suggests that six possible novel epitopes as VEPGQLKLSWFKKGSSIGQM, TELKYSWKTWGK, NDWDFVVTTDIS, AKKQDVVLGSQEGAM, EIAETQHGTIVVRVQYEGDG, and DGITVIDLDPIPYDPK is expected to be unreported peptides.
Keywords: Dengue virus, B-cell epitopes, antigenicity, dengue, vaccine